Original and generic medicines: clinical, economic and social aspects in the context of health care systems - Lewandowski, Marcin; Religioni, Urszula; Agnieszka, Barańska; Krystian, Wdowiak; Kobayashi, Adam; Borowska, Mariola; Marcin, Czech; Piotr, Wierzbiński; Daniel, Śliż; Katarzyna, Plagens–Rotman; Merks, Piotr (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2025)
This narrative review synthesizes evidence on clinical, regulatory, economic, and social aspects of generic drug use, focusing on European and Polish contexts. We searched MEDLINE/PubMed, Embase, Scopus, Web of Science, Cochrane Library, and regulatory sources for English and Polish-language records published January 2015 to October 2025. Regulatory authorities apply rigorous bioequivalence and Good Manufacturing Practice standards ensuring generics meet the same quality requirements as branded counterparts. Across most small-molecule indications, these standards predict comparable therapeutic outcomes, with residual caution for narrow-therapeutic-index or modified-release medicines. Despite regulatory assurance, perceptions of inferiority persist among healthcare professionals and patients, influenced by misinformation, inconsistent communication, and branding cues. Economically, generics consistently reduce public and out-of-pocket expenditures and enable reinvestment in innovative therapies. Policy tools such as reference pricing, INN prescribing, and pharmacist substitution shape uptake, though implementation varies. Supply-chain vulnerabilities and market-sustainability pressures threaten continuity of access. Four priority actions emerge: improve transparency of regulatory decisions and product-level information at point of care, standardize professional and public education on generic equivalence, protect sustainable competition through calibrated pricing and diversified sourcing, and prioritize real-world comparative research in sensitive indications. These measures would strengthen trust, ensure reliable access, and allow savings to be reinvested in high-value innovation.